2009
DOI: 10.1249/mss.0b013e3181a24536
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Type, Duration, and Intensity of Physical Activity Using an Accelerometer

Abstract: This study demonstrated the ability of a triaxial accelerometer in detecting type, duration, and intensity of physical activity using models based on acceleration features. Future studies are needed to validate the presented models in free-living conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
199
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 31 publications
4
199
1
Order By: Relevance
“…Differences in performance between the classification models are small, with the SVM and the majority voting scheme achieving slightly higher accuracy. Other studies using similar schemes have reported accuracies that are comparable to what is presented in this study (93% [25], 94-100% [24], 90.1% [26]). Although all models showed high aggregated performance when evaluated using a leaveone-subject-out cross-validation, the class-specific F-scores revealed that one particular class was difficult to distinguish from the others.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Differences in performance between the classification models are small, with the SVM and the majority voting scheme achieving slightly higher accuracy. Other studies using similar schemes have reported accuracies that are comparable to what is presented in this study (93% [25], 94-100% [24], 90.1% [26]). Although all models showed high aggregated performance when evaluated using a leaveone-subject-out cross-validation, the class-specific F-scores revealed that one particular class was difficult to distinguish from the others.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have also focused on using more unobtrusive sensors to detect simpler activities. Classification models, when trained and evaluated using data collected with a single accelerometer in laboratory sessions, have shown promising performance and a high success rate: 94-100% [24], 93% [25], 90.8% [26] and 89% [19]. However, the reproducibility of the performance achieved by these models in daily life is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Advances have, however, been made in accelerometer data processing with the development of more sophisticated approaches to data modelling analysis (Bonomi et al 2009, Pober et al 2006, Staudenmayer et al 2009, Zhang et al 2003. This area warrants further investigation in studies of pre-school children to determine if this will offer an accurate means of classifying physical activity behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that identifying three different postures, that is, lying, sitting and standing, and three types of locomotion movements, that is, walking, running and cycling, was accurately achieved using a single accelerometer positioned at the waist. 54 However, standing was often confused with sitting and for this reason in later studies 55 the sitting and standing classes were combined together in a single category describing static events. Multiple accelerometers allow the successful distinction between sitting and standing.…”
Section: Activity Recognition Using Multiple or Single-site Accelerommentioning
confidence: 99%